Thursday

April 17, 2014

April 17, 2014

Posted by **pervaiz** on Monday, April 20, 2009 at 5:05pm.

f(x)=(e^(-x)^2) -1+(x^2)

and

g(x)=x cos (x/square root 3)

- calculus (#1` of 2) -
**drwls**, Monday, April 20, 2009 at 5:58pmf(x)=(e^(-x)^2) -1+(x^2)

= 1 - x^2 + x^4/2! - x^6/3! + ... -1 + x^2

= x^4/2! - x^6/3! + x^8/4! - ...

**Related Questions**

Calculus - Find a power series, centered @ x=0, for function f(x)=x/(1+2x). I ...

Calculus - Find a power series, centered @ x=0, for function f(x)=x/(1+2x). I ...

Calculus 2 - The following function has a series of the form the sum from n=0 to...

Calculus - Obtain the MacLaurin series for 1/(2-x) by making an appropriate ...

Calculus II - (a) Use differentiation to find power series representation for f(...

calculus - power series ASAP please :) - using power series, integrate & ...

Calculus - This is going to be pretty hard to show as text since it would be ...

Calculus - a) Find the Taylor series associated to f(x) = x^-2 at a = 1. Be sure...

College Calculus (Binomial Series) - Expand f(x) = (x+x^2)/((1-x)^3) as a power ...

Calculus - Taylor #2 - Find the Taylor series for f(x) centered at the given ...